Learning while Playing at Early Childhood Stage - Son, Romila (THE PRIMARY TEACHER, 2011)
The first six to eight years of a child’s life, known as the early childhood stage, are globally acknowledged to be the most critical years for life-long development, since the pace of development in these years is extremely rapid. Recent research in the field of neuroscience, particularly on the brain has provided very convincing evidence of the ‘critical periods’ located within these early years, particularly the first three years, for forming of synaptic connections in the brain, and for the full development of the brain’s potential. Research has also indicated that if these early years are not supported by, or embedded in, a stimulating and enriching physical and psycho-social environment, the chances of the child’s brain developing to its full potential are considerably and often irreversibly reduced. This finding immediately places a very large percentage of children in the developing world in poverty contexts ‘at risk’, in terms of their life chances. The early childhood stage in life is also important as a foundation for inculcation of social and personal habits and values which are known to last a lifetime. What follows logically is the crucial importance of investing in these early years to ensure an enabling playful environment for every child and thereby, a sound foundation for life, which is not only the right of every child but will also impact, in the long term, on the quality of human capital available to the country.